Pre-flood disaster coordination and management mobile app / Muhammad Syafiq Othman - Othman, Muhammad Syafiq (2018)
Smart phones have become essential items in our daily to keep us update including informing of news and disasters. One relevant example of the disaster in Malaysia is flood that brings damaged annually. However, preparation for flood management is still not efficient. Hence, we propose to overcome this problem by developing a mobile application that can assist the coordination and management of flood preparation. This real-time application can store the relevant parameters information that are requested such as shelters, foods, agencies and equipment. The project methodology is adapted from ADDIE, where from the phases, only four phases are executed: Analysis, Design, Develop and Testing. From the test, it shows that the system is update in real-time and it is secure since the user have to sign in first before they can update the database. The app was tested based on a survey of 10 users. Thus, by having a system can provide the management a better preparation could bring a better result in flood effect.